BEBAN KERJA PERAWAT DAN KINERJANYA. STUDI KASUS DI "RS UMUM PEKERJA PT KAWASAN BERIKAT NUSANTARA" JAKARTA TAHUN 2022 - Galuh Larasati (2022)
Nurse performance is results from nurses working and carrying out nursing functions for patients. The good and bad performance of nurses can be related to how much nurses bear the physical and mental workload. The purpose of this study was to determine the difference in the average performance of nurses between nurses with light, moderate, and heavy physical workloads and the differences in the average performance of nurses between nurses with light, medium, and heavy mental workloads at RS Umum Pekerja PT Kawasan Berikat Nusantara. This study used a quantitative method with a cross-sectional research design with questionnaire and a fingertip pulse oximeter. The sample is 87 respondents with total sampling technique. The results of the bivariate analysis showed that there was a difference in the average performance of nurses in the physical workload category (p-value 0.000) and the mental workload category (p-value 0.000). The study concludes that the performance of nurses is influenced by the physical and mental workload. That way, the company needs to hold a meeting to discuss the causes, impacts, and how to overcome the physical workload and mental workload so the performance of nurses is not disturbed.